Reverse NCX Attenuates Cellular Sodium Loading in Metabolically Compromised Cortex. (9th November 2017) - Gerkau, Niklas J; Rakers, Cordula; Durry, Simone; Petzold, Gabor C; Rose, Christine R
Abstract: In core regions of ischemic stroke, disruption of blood flow causes breakdown of ionic gradients and, ultimately, calcium overload and cell death. In the surrounding penumbra, cells may recover upon reperfusion, but recovery is hampered by additional metabolic demands imposed by peri-infarct depolarizations (PIDs). There is evidence that sodium influx drives PIDs, but no data exist on PID-related sodium accumulations in vivo. Here, we found that PIDs in mouse neocortex are associated with propagating sodium elevations in neurons and astrocytes. Similar transient sodium elevations were induced in acute tissue slices by brief chemical ischemia. Blocking NMDA-receptors dampened sodium and accompanying calcium loads of neurons in tissue slices, while inhibiting glutamate transport diminished sodium influx into astrocytes, but amplified neuronal sodium loads. In both cell types, inhibition of sodium/calcium exchange (NCX) increased sodium transients. Blocking NCX also significantly reduced calcium transients, a result confirmed in vivo. Our study provides the first quantitative data on sodium elevations in peri-infarct regions in vivo. They suggest that sodium influx drives reversal of NCX, triggering a massive secondary calcium elevation while promoting export of sodium. Reported neuroprotective effects of NCX activity in stroke models might thus be related to its dampening of ischemia-induced sodium loading.